Between Development and Sustainability: Symbiotic Synergy or Irreconcilable Duality - Agata Ferreira (The Central European Review of Economics and Management (CEREM), 2017)
Aim: This paper studies the concept of sustainable development, which has been overly present in recent times on global arena of debates about issues most pressing to humanity in variety of contexts, political, legal, social and environmental. It has been appropriated by governments and NGOs alike. It is being advocated to promote both, continuous growth and reversal of unsustainable pattern of limitless growth. The aim of this paper is to follow the history of the concepts of development and sustainability, its evolution and current status and question whether future developments in the area of sustainable development are likely to support "development" part of it, through drive to maximum economic growth, increase of financial flows and investments, consumption and production; or whether the "sustainability" part of the agenda, with protection of environment, human rights and climate as a priority, will prevail.Design / Research methods: The article follows the historical origins and developments of the concepts of development and sustainability, since industrial revolution of the eighteenth century where progress has been linked with economic growth and material advancement. The concept of sustainability on the other hand is closely connected with human relationship with nature, which went through a profound change when people started to make permanent settlements, domesticate animals and farm the land. This paper explains how sustainable development term rose to political prominence following publication of the Brundtland report in 1987 and how subsequent global political initiatives, like Agenda 21, Johannesburg Declaration and 2030 Agenda, gradually reaffirmed the place of sustainable development as an important element of international agenda and broadened the meaning of the term.Conclusions / findings: The role of business partner is present in 10% of the examined enterprises, with the source of capital and the entity size being of minor importance. Projects play a key role in the development of contemporary undertakings. Moreover, the primary role in terms of the implementation of any organizational activities is exercised by people. Thus, the opportunity emerges to implement and modify the concept of HR business partnering. This will lead to a greater professionalization of staffing, which will ultimately affect positively the implementation of strategy of the organizations under discussion.Originality / value of the article: The publications on project management as well as those concerned with human resources management have so far not addressed the issue of the development of the HR business partner role in the organizations under discussion. The considerations, of both theoretical and practical nature, contribute to the theory of management, being much relevant owing to the ever growing popularity of the concept of management through projects. – – Cel: Artykuł prezentuje koncepcje zroẃnowazȯnego rozwoju, ktoŕa w ostatnim czasie jest silnieobecna na globalnej scenie debat nad kwestiami najwazṅiejszymi dla ludzkosći, w rozmaitychkontekstach politycznych, prawych, społecznych i sŕodowiskowych. Koncept został przywłaszczonyprzez rzady i organizacje pozarzadowe. Postuluje on promowanie zaroẃno ciagłego wzrostu, jak iodwroćenie tendencji nieograniczonego wzrostu. Celem niniejszego artykułu jest przesĺedzenie historiikoncepcji rozwoju i zroẃnowazȯnego rozwoju, jego ewolucji i aktualnego stanu oraz kwestionowanie,czy przyszłe zmiany w obszarze zroẃnowazȯnego rozwoju przyczynia sie do wspierania "rozwoju",poprzez dazėnie do maksymalnego wzrostu gospodarczego, przepływoẃ kapitału i inwestycji,konsumpcji i produkcji; czy wazṅa jest kwestia "zroẃnowazėnia" i uwzglednienia ochrony sŕodowiska,praw człowieka i klimatu jako priorytetu.Układ / Metoda badawcza: Artykuł przedstawia historyczne pochodzenie i rozwoj́ koncepcji rozwojui zroẃnowazȯnego rozwoju, od rewolucji przemysłowej z XVIII wieku, gdzie postep utozṡamiany byłze wzrostem gospodarczym i postepem materialnym. Z drugiej strony koncepcja zroẃnowazȯnegorozwoju jest sćisĺe zwiazana z relacjami człowieka z natura, ktoŕa to przeszła głeboka zmiane, gdyludzie zaczeli zakładacśtałe osady, udomowiacźwierzeta i uprawiacźiemie. W tym artykulewyjasńiono, jak koncept zroẃnowazȯnego rozwoju urośł do politycznego znaczenia po publikacjiraportu Brundtland w 1987 roku i jak kolejne globalne inicjatywy polityczne, takie jak Agenda 21,deklaracja z Johannesburga i Agenda 2030 poszerzyły znaczenie tego terminu i potwierdziły, zėkoncept zroẃnowazȯnego rozwoju stanowi wazṅy element miedzynarodowego porzadku.Wnioski/wyniki: Artykuł podsumowuje, zė głoẃny kontekst zroẃnowazȯnego rozwoju koncentrujesie na utrzymaniu wzrostu gospodarczego, ktoŕy nadal pozostaje głoẃnym celem globalnym, zewzrostem sẃiadomosći ekologicznych zagrozėnd́la planety jedynie jako tło, na ktoŕym ciagły wzrostgospodarczy wymaga podtrzymania.Oryginalnosć\' / Wartosćártykułu: Niniejsza praca ilustruje, w jaki sposob́ koncept zroẃnowazȯnegorozwoju urośł w skali globalnej, a tym samym stracił na znaczeniu, bedac utozṡamiany niemal zewszystkim.
Keywords: B0; F0; O1; Q5; 330; sustainable development; economic growth; 2030 Agenda; sustainability; environment